Effect of oxygen on the radiation of silicone rubber determined by gaseous chromatograph and DFT calculation - Lei Yu; Shuai Liu; Bo Liu; Zhenghao Mao; Wei Huang; Jing Peng; Yinyong Ao (Nuclear Analysis)
The radiation effects of silicone rubber under different atmospheres are of great significance to evaluate the aging behavior of materials, and to assess their practical application life. The radiation-induced cross-linking and degradation of polydimethylsiloxane rubber were confirmed firstly by 1H NMR and high-temperature GPC, respectively. By using the established gas collecting system and gaseous chromatography method, we systematically investigated the gaseous products of irradiated silicone rubber at different oxygen concentrations. With the increase of oxygen concentration, the yield of CH4 decreases sharply, while the yield of hydrogen changes slightly. It can be further demonstrated that the reduction of CH4 concentration in the irradiated silicone rubber system is mainly due to the inhibition of CH4 formation, instead of the CH4 degradation, indicating that oxygen directly influences the conversion process of methyl radicals. Similarly, by monitoring the oxygen consumption, it is proved that oxygen is directly involved in the degradation process of silicone rubber, and oxygen scavenged the methyl radicals, which supressed the conversion process of methyl radicals to CH4. Finally, the radiation-induced crosslinking and degradation mechanism of raw silicone rubber was deduced by combining the gaseous products analysis and DFT calculation. It is demonstrated that the release of CH4 can be used to assess the radiation effect of silicone rubber. This work provides a novel method to understand deeply the radiation-induced crosslinking and degradation mechanism of silicone rubber under different atmospheres.